1998
DOI: 10.3354/cr009197
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the daily temperature range annual cycle in the United States

Abstract: Many researchers are presently interested in detecting long-term trends in annual or seasonal daily temperature range (DTR), and attributing these changes to anthropogenic origins. However, very little work has been done to confirm the mechanisms that are important to determining the long-term average annual cycle of the DTR. Therefore, the focus of this work is to examine the spatial and temporal difference in the DTR average annual cycle across the United States, and to associate the patterns of these cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Diurnal air temperature variations of at least 24°C are possible (Leathers et al, 1998, data for Wilcox, AZ) in near-surface desert environments, with even higher values possible within surface clasts. This variation causes surface clasts to expand and contract, generating mechanical stresses within the rock.…”
Section: Introductionmentioning
confidence: 96%
“…Diurnal air temperature variations of at least 24°C are possible (Leathers et al, 1998, data for Wilcox, AZ) in near-surface desert environments, with even higher values possible within surface clasts. This variation causes surface clasts to expand and contract, generating mechanical stresses within the rock.…”
Section: Introductionmentioning
confidence: 96%
“…Robinson et al (1995) and Leathers et al (1998) demonstrated large-scale changes in DTR are associated with seasonal progression. It is suggested earlier in this paper that the decreases in daytime mean maximum temperature and DTR in irrigated locations are related to greater evapotranspiration and a larger amount of energy partitioning to latent heat.…”
Section: Discussionmentioning
confidence: 95%
“…The study area (Montreal, Canada) experienced relatively greater DTR (up to 28.1°C) than Asian regions (up to 16°C) (Kan et al 2007). Spatial and temporal DTR variability may be caused by land use type (Scheitlin and Dixon 2010;Bonan 2001;Gallo et al 1996), season (Durre and Wallace 2001a, b;Leathers et al 1998), latitude (Durre and Wallace 2001b;Leathers et al 1998), water vapor (Sun et al 2006), and air mass type (Scheitlin and Dixon 2010). Accounting for DTR variability across the nation, it is important to investigate the association between DTR and mortality in the USA.…”
Section: Introductionmentioning
confidence: 98%